2004
DOI: 10.1002/tea.20029
|View full text |Cite
|
Sign up to set email alerts
|

Making a difference for minorities: Evaluation of an educational enrichment program

Abstract: A comprehensive, quantitative evaluation of an educational intervention program designed to reduce the attrition of minorities from the biological sciences was undertaken to ascertain whether such efforts adequately address the problem. Program participants had greater odds of persisting in basic math and science courses, and of graduating in biology, than did a comparison group, controlling for demographics and academic preparation. Undergraduate research greatly increased the odds of positive graduation outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 5 publications
12
142
0
2
Order By: Relevance
“…Researchers have also studied the benefits of undergraduate research programs (Allen & Zepeda, 2007;Barlow & Villarejo, 2004;Carter, Mandell, & Maton, 2009;Chatman, 2005;Eagan, et al2010;Hathaway, Nagda, & Gregerman, 2002;Maton & Hrabowski, 2004;Seymour, Hunter, Laursen, & DeAntoni, 2004). In particular, some research has demonstrated that such programs may increase students' decision to pursue post-baccalaureate studies.…”
Section: Student Research Opportunitiesmentioning
confidence: 99%
“…Researchers have also studied the benefits of undergraduate research programs (Allen & Zepeda, 2007;Barlow & Villarejo, 2004;Carter, Mandell, & Maton, 2009;Chatman, 2005;Eagan, et al2010;Hathaway, Nagda, & Gregerman, 2002;Maton & Hrabowski, 2004;Seymour, Hunter, Laursen, & DeAntoni, 2004). In particular, some research has demonstrated that such programs may increase students' decision to pursue post-baccalaureate studies.…”
Section: Student Research Opportunitiesmentioning
confidence: 99%
“…Research experiences also have been shown to boost URM-specific retention, academic achievement, and graduate school enrollment (Barlow and Villarejo 2004;Foertsch et al 1997;Jonides 1995). For example, a University of Michigan undergraduate research program for first-and second-year students found that participation contributed to lower attrition rates, higher grades, and positive effects on self-esteem (Nagda et al 1998).…”
Section: Research and Theory Guiding The Studymentioning
confidence: 99%
“…Becoming involved in scientific research early in college indicates a potentially strong commitment to pursuing not only a science major but also an advanced science degree, as previous research points to the importance of undergraduate research experiences in encouraging students to go on to graduate study (Barlow and Villarejo 2004). To the extent that URM students understand how participating in a structured research program improves their likelihood of reaching their educational goals, they may seek out research experiences as early as their first year of college.…”
Section: Goal Commitment and Academic Engagementmentioning
confidence: 99%
See 2 more Smart Citations